Medical Devices – From Licensing To Coverage: Highlights From Argentina, Brazil, Colombia, And Mexico - Rey Ares, Lucila (2015)
Objectives: To assess, describe and compare the requirements and pathwaysof medical devices from licensing to coverage in four Latin American countries(LAC) health systems. Methods: We conducted a literature search (February 2015)on Pubmed, Lilacs and Value in Health Regional Issues journal. We also searchedspecific websites of Health Technology Assessment (HTA) and regulatory agencies,ministries of health and health agencies; and a performed generic Internet search.We included all publications describing aspects related to regulation, coverage,medical technology innovation, and HTA and Economic Evaluation (EE) guidelines.We additionally interviewed key informants from all countries to gather informationrelated to the aforementioned processes. We present here the literature searchresults. Results: We included 60 studies out of 2190. Five percent of the publicationsanalyzed the four countries jointly, 75% were from Brazil, 8.3% from Mexico, 5%from Colombia and 5.7% from LAC in general. Half of the studies described the roleof the HTA and EE in decision-making and aspects or policies related to innovation(25% and 23.3%). Regarding the description of the coverage process, it was addressedin 13.3% of the studies; 10% of the publications focused on technovigilance; and also10% on regulatory aspects. Remaining publications were methodological guidelinesand general descriptions of the health systems and the role of medical devices. Allcountries had HTA and EE guidelines, although there did not include device specificrecommendations. There is a spectrum of HTA formalization for technology incorporationafter licensing, higher in Brazil and lower in Argentina Conclusions:There is scarce information on the processes and requirements to achieve coveragefor medical devices in these countries. Processes differ, are in general not explicit,lack transparency, and usually replicate those of drugs not taking into account thespecificities of medical devices.